Implementasi Program Puskesmas Terhadap Penanggulangan Kejadian Berat Bayi Lahir Rendah (BBLR) di Kota Salatiga - Lesnussa, Merya Meisce C (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Low birth weight (LBW) is a baby born weighing less than 2500 grams which causes infant mortality rate (IMR). The purpose of this study is to describe the implementation of the Puskesmas program in preventing LBW in Salatiga City.Method: The research uses a qualitative method with a case study approach. Also, data collection techniques are in-depth interviews using an interview guide as a research instrument. Moreover, the research participants were 4 health workers. Meanwhile, data analysis techniques were data reduction and conclusion drawing. Also to support this research, the researcher used narrative presentation of data.Results: Therefore, the results showed 5 LBW prevention programs at the Sidorejo Kidul Health Center, in the form of a complete ANC 10T examination service. The giving supplementary Feeding (PMT) in the form of biscuits, green beans, sugar, margarine, eggs, regal, and shredded for 3 months. Neonatal visits (KN) are carried out at health facilities or home visits using the integrated management of young toddlers (MTBM). The maternal care group (KSI) consists of health workers, cross-sectors, and cadres who monitor and collect data on the target group. The class for pregnant women is carried out by providing education to pregnant women and their closest family which includes pregnancy, childbirth and the postpartum period.Conclusion: Thus, the researcher concluded that the Puskesmas program for the prevention of LBW events has been implemented.